El cine tiene cuerpo de mujer - Hatfield, Elia (Colección Ensayo ;, 2018)
Essays on discourse of female body and its representations in film. Is based particularly on analysis of late 20th-century films starring actress and politician Maria Rojo. Analyzes ways in which her characters subvert stereotypical constructions of body and portrays movement of avant-garde filmmakers to question male-dominated discourse of films made in 1950s-1970s.